Exploring the impact of shared mobility services on CO2 - Tikoudis, Ioannis (OECD Publishing, 2021)
Policy action to avoid the impending societal costs of climate change is particularly warranted in transport sector, which is responsible for 30% of greenhouse gas emissions in OECD countries. To design appropriate interventions in this sector, policy makers should account for the recent emergence of shared mobility services in urban areas and their potential advantages in terms of emissions mitigation. This study estimates the impact that the widespread uptake of shared mobility services could have on the carbon footprint of urban transport. To this end, it simulates the share of each transport mode and aggregate emissions from passenger transport in 247 cities across 29 OECD countries between 2015 and 2050. The analysis indicates that they have the potential to eliminate, on average, 6.3% of urban passenger transport emissions by the end of this period
Keywords: Environment; Transport